No clinically meaningful weight changes in a young cohort following total joint arthroplasty at 3‐year follow‐up. Issue 1 (30th November 2016) - Formby, Peter M.; Purcell, Richard L.; Baird, Michael; Wagner, Matthew; Goodlett, Ronald P.; Mack, Andrew W.
Abstract : Background: Total joint arthroplasty (TJA) is one of the most successful operations. There is little in the literature regarding weight change following TJA, particularly in a young cohort. Methods: Retrospective analysis of 181 primary total hip arthroplasty (THA) and 185 primary total knee arthroplasty (TKA) patients was conducted. We reviewed preoperative and post‐operative weights and post‐operative body mass index at 3 and 6 months, 1 year, 2 and 3 years. We evaluated expected versus actual weight gain, and performed subgroup analyses of obese versus non‐obese patients and active duty versus civilian patients. We used a minimal clinically meaningful weight change from baseline of ≥5%. Results: One hundred and fifty‐one (41.3%) patients were active duty military service members with the mean age of 53 ± 11.1 years. In TKA patients, statistically significant differences were found in mean weights at 3 months (−1.8%, P  ≤ 0.0001) and 2 years (+1.9%, P  = 0.0006). In THA patients, statistically significant weight gains were found at 6 months (+1.1%, P  = 0.006). For obese TKA patients, significant weight changes were observed at 3 months (−2.5%, P  ≤ 0.0001), and none in the obese THA group. There were no statistical or clinically meaningful weight changes in the non‐obese TKA or THA groups. There was a clinically meaningful weight gain in active duty TKA patients at 3 years (5.18%, P  = 0.17). Conclusion: Despite a theoretical ability to lose weight following TJA, patients maintain their preoperative weight following TJA. We found a clinically meaningful weight gain at 3 years post‐operatively only in active duty TKA patients. Overall, however, we found no clinically significant weight changes following TJA at 3‐year follow‐up.